Early Experience of Microsurgical Clipping of Ruptured Intracranial Aneurysms - Nepal, Pankaj Raj (Nepal Journal of Neuroscience, 2019)
To see the outcome in patients following microsurgical clipping of ruptured intracranial aneurysms and analyze the results. It is a prospective analytical study were demographic data of the patient, initial World Federation of Neurosurgical Societies (WFNS) grade, Fischer’s grade, duration of ictus, intra operative rupture, incidence of clinical vasospasm and Modified Rankin Scale (MRS) at three months were collected and analysis was done using SPSS-20. There were total 19 cases of microsurgical clipping, with mean age 55.4 yrs, where 52.4% were females. Average duration of Ictus was 24.5 hours. Most common WFNS grade on presentation was grade II (42%) and Fischer’s CT grade was IV (58%). Commonest site of aneurysm was A Com (53%) and were 15.8% intraoperatie rupture. Ventriculo-peritoneal (VP) shunt and severe clinical vasospasm both were seen in 10.5%. Overall mortality was 11% and MRS 1 and 2 were obtained in 10% and 58% respectively. Good initial WFNS, internal carotid aneurysm, absence of hydrocephalus and absence of clinical vasospasm were significantly associated with better MRS at three months. Factors associated with better outcome were good initial WFNS, internal carotid aneurysm, absence of hydrocephalus and absence of clinical vasospasm.